On The Numerical Solution Of Differential-Algebraic Equations With Index-2 By Chebyshev Approximation - Yeloglu, Turgut; Celik, Ercan (CENTRE ENVIRONMENT SOCIAL & ECONOMIC RESEARCH PUBL-CESER, 2008)
In this paper, numerical solution of differential-algebraic equations with index-2 is considered. First Index- 2 system is reduced to index-1 system. Then we have applied the Chebyshev Approximation method for solving differential-algebraic equations with index-2 numerically.
Keywords: Differential-algebraic equations (DAEs); Power Series; Index-1; Index-2; Chebyshev Series Approximation; Mathematics